2010
DOI: 10.4161/psb.5.8.12407
|View full text |Cite
|
Sign up to set email alerts
|

Roles of calcineurin B-like protein-interacting protein kinases in innate immunity in rice

Abstract: Cytosolic free Ca(2+) mobilization induced by microbe/pathogen-associated molecular patterns (MAMPs/PAMPs) play key roles in plant innate immunity. However, components involved in Ca(2+) signaling pathways still remain to be identified and possible involvement of the CBL (calcineurin B-like proteins)-CIPK (CBL-interacting protein kinases) system in biotic defense signaling has yet to be clarified. Recently we identified two CIPKs, OsCIPK14 and OsCIPK15, which are rapidly induced by MAMPs, involved in various M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Our results and other recent reports that suggest the participation of rice CIPK14/15 in regulation of defense gene expression and phytoalexin production in rice cultured cells and the possible regulation of NPR1 by PKS5 (Arabidopsis CIPK24) phosphorylation (Kurusu et al, 2010;Xie et al, 2010) support a role for CBL/CIPK participation in different aspects of plant defense. Thus, CBL/CIPK complexes are important players in modulating outputs during biotic interactions.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results and other recent reports that suggest the participation of rice CIPK14/15 in regulation of defense gene expression and phytoalexin production in rice cultured cells and the possible regulation of NPR1 by PKS5 (Arabidopsis CIPK24) phosphorylation (Kurusu et al, 2010;Xie et al, 2010) support a role for CBL/CIPK participation in different aspects of plant defense. Thus, CBL/CIPK complexes are important players in modulating outputs during biotic interactions.…”
Section: Discussionsupporting
confidence: 67%
“…SOS1, a Na + / H + antiporter, which is a target of the SOS3/SOS2 complex, has been reported to be posttranscriptionally regulated by ROS and to interact with oxidative responses regulators (Katiyar-Agarwal et al, 2006;Chung et al, 2008). In rice cultured cells treated with PAMPs, CIPK14/15 appear to mediate ROS production (Kurusu et al, 2010), and, more recently, Arabidopsis CIPK26 was shown to interact with RBOHF in planta and positively and negatively regulate its ROS-producing activity in human cultured cells (HEK293T) (Kimura et al, 2012;Drerup et al, 2013). In planta validation of such results in the context of a specific physiological response will consolidate these promising results.…”
Section: Discussionmentioning
confidence: 99%
“…A function of a rice CIPK has been reported for OsCIPK31, which was found to modulate responses to abiotic stresses during seed germination and seedling growth (Piao et al, 2010), and OsCIPK23, which turned out to be a multistress-induced gene likely regulating signaling pathways during pollination and drought stress responses (Yang et al, 2008). Another example for a multifunctional rice CIPK is OsCIPK15, which has been implicated in mediating oxygen deficiency tolerance as well as being involved in various PAMPinduced immune responses together with OsCIPK14 (Lee et al, 2009a;Kurusu et al, 2010). Comparative structural analyses of CBLs and CIPKs from Arabidopsis, pea (Pisum sativum), and rice revealed a high degree of conservation, and additional functional analyses suggested comparable mechanisms underlying signal transduction via CBL-CIPK complexes from these species (Mahajan et al, 2006;Tuteja and Mahajan, 2007).…”
Section: The Cbl-cipk Network Is Conserved In Many Plant Speciesmentioning
confidence: 99%
“…OsMPK6 whose activation is regulated by OsTPC1 may also participate in the induction of phytoalexin biosynthesis induced by TvX. OsCIPK14/15 activated by binding of calcineurin B-like Ca 2ϩ sensor proteins are involved in various layers of TvX-induced defense responses including the expression of the same diterpene cyclase genes and phytoalexin production (9,53). The phenotypes of knockdown cell lines of the CIPKs (9) are similar with those of OsTPC1 (Fig.…”
Section: Tvx Triggered a Prolonged Increase In Cytosolic Camentioning
confidence: 57%